THE PICTURE AS A RESULT OF MEMORY IN NEMERE KEREZSI’`S ART - Anastasiei, Iolanda (Design/Arts/Culture, 2023)
In this paper I focus on a case study concerning Nemere Kerezsi’s artistic approach presented in the exhibition Nemere Kerezsi: Thiemann-Etüde (Quadro Gallery, Cluj-Napoca, 13th of May – 24th of June 2022). The aim of this article is to analyze the close relationship between memory and image, starting from the way the artist observes and researches the memory and narratives created around places, which he claims as the central resource for the creation of his works present in the Thiemann-Etüde exhibition. The artist systematically starts from the micro framework of personal memories and narratives, which are then recorded and reproduced, through suggestive images, for the macro framework of the Anthropocene topic of the current history. Thus, the theoretical debates on the issue of the Anthropocene are relevant in this context, because the artist captures through a diversified visual language (video, photography, sculpture, installation etc.) the cultural-artificial intervention of man on nature and the consequences of this intrusion. Starting from the premise that the natural environment and history present themselves more and more as a result built on the basis of the interconnection of people who fabricate communities, Nemere Kerezsi developed his artistic approach similar to anthropological research. Namely, the artist collects subtle data about the personal memory of different places he’s visited, in order to generate the “image of an experience”.